Hubungan Tingkat Pengetahuan Ibu Terhadap Kelengkapan Imunisasi Dasar Lengkap Pada Bayi 0-11 Bulan di Wilayah Puskesmas Mertoyudan 1 - Maymona; Dian Monalisa Rusliana; Evy Ernawati (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Background: Immunization is one of the key efforts to enhance immune protection and to eradicate infectious diseases, but many infants have not yet received a complete schedule of immunizations. According to data from Puskesmas Mertoyudan I, 87.99% of infants and toddlers have completed the basic immunization schedule, and maternal knowledge of the importance of immunization plays a crucial role in determining immunization completeness. Objective: This study is to examine the relationship between mothers’ level of knowledge and the completeness of basic immunization among infants aged 0–11 months. Methods: A non-experimental research design with descriptive analysis was conducted using a cross-sectional approach. The population consisted of mothers who had infants aged 0–11 months. The sample was selected using a simple random sampling technique, consisting of 92 respondents. Data analysis was performed using the Chi-square test. Results: The majority of respondents had less than adequate knowledge, accounting for 53 respondents (57,6%), and the majority had completed the basic immunization, totaling 58 respondents (63%). The results of the Chi-square test indicated a significant relationship between maternal knowledge level and the completeness of the basic immunization schedule among infants aged 0–11 months in the Puskesmas Mertoyudan I service area, Magelang Regency (p < 0.001). Conclusion: There is a significant association between maternal knowledge level and the completeness of basic immunization among infants aged 0–11 months in the Puskesmas Mertoyudan I, Magelang Regency.